Growth performance and digestive enzyme activities of fringe-lipped carp Labeo fimbriatus (Bloch, 1795) in periphyton based nursery rearing system - Gangadhar, B.; Sridhar, N.; latha, Uma; Raghavendra, C. H.; Santhosh, H. J.; Jayasankar, P. (Indian Journal of Fisheries, 2016)
Nursery rearing of Labeo fimbriatus was undertaken in outdoor cement tanks with soil base, where periphyton growth was enhanced by providing sugarcane bagasse as substrate. The growth parameters in terms of final weight of fish, weight gain and biomass were the highest under Substrate + Feed treatment. Growth of fish under Substrate only treatment was comparable with that of the Control. No difference was observed with respect to final length and survival of fish between treatments. Activity of digestive enzymes corroborated the growth pattern. Enhancing periphyton growth can be an alternative for artificial feeding in nursery rearing of L. fimbriatus.